ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI JAGUNG - Akbar Habib (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2013)
The experiment was conducted using the case study method. Aims to analyze how much influence the use of factors of production, namely land area (X1), seeds (X2), fertilizer (X3), the production of maize (Y). Value of coefficient of determination (R2) in this study was 0.99, meaning that the influence of the factors of production to production can be explained by the four independent variables (X) of 99%, the rest is explained by other factors outside of the study. F value - count 19.45> F-table at 2.78 level of 95% thus H1 is accepted and H0 is rejected. Simultaneously means there is a real influence among broad land, seed, fertilizer, and labor to the production of corn. Partially significantly affect seed production, while the area of land, fertilizer, and labor did not significantly affect corn production. From the calculation results obtained scale RTS value = 0.98, thus smaller than the RTS (εp <1) then this indicates a state of decreasing returns to scale, which means additional input of land, seed, fertilizer, and labor respectively - each additional 1% exceeded production by 0.98%.Keywords: factors of production, production, Return to Scale